Butterfly garden - Harris, Sue.; Boey, Stephanie (San Francisco : Chronicle Books, 2006)
Tabby Cat looks all over the garden for butterflies to play with and finally finds them in a surprising place.
Keywords: Cats -- Juvenile fiction; Butterflies -- Juvenile fiction; Gardens -- Juvenile fiction